2017
DOI: 10.17235/reed.2017.4518/2016
|View full text |Cite
|
Sign up to set email alerts
|

Coping with celiac disease: how heavy is the burden for caregivers?

Abstract: Background: Celiac disease (CD) is the most common chronic enteropathy demanding a lifelong gluten-free diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is not clear which of these targets should be considered as the primary or secondary endpoint of GFD for CD patients towards their long-term prognosis [6]. Although safe and efficient, GFD is very restrictive, resulting as a burden on social life and quality of life (for both patients and caregivers) [7][8][9][10] and frequently with poor compliance [11][12][13]. Moreover, the clinical response to inadvertent or voluntary gluten ingestion by treated CD patients can be very heterogeneous, ranging from gastroenteritislike pictures to no symptoms [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear which of these targets should be considered as the primary or secondary endpoint of GFD for CD patients towards their long-term prognosis [6]. Although safe and efficient, GFD is very restrictive, resulting as a burden on social life and quality of life (for both patients and caregivers) [7][8][9][10] and frequently with poor compliance [11][12][13]. Moreover, the clinical response to inadvertent or voluntary gluten ingestion by treated CD patients can be very heterogeneous, ranging from gastroenteritislike pictures to no symptoms [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…Their quality of life is known to improve once CD cases have been diagnosed and started on a gluten-free diet. 29,30 One review study involving caregivers of individuals with chronic disease emphasized the need for caregivers to be educated about the disease, for health workers to share their treatment plans with the caregiver, and for caregivers to be provided with social and material support and support in terms of coping with the disease. 23 The present study revealed the need for caregivers of pediatric CD cases to receive more evaluation in terms of burden.…”
Section: Discussionmentioning
confidence: 99%
“…The data from the present study show that individuals caring for such cases should also be evaluated in terms of burnout at routine clinical examinations of pediatric CD cases. In a study from Italy, Ferretti et al 29 reported that alarm symptoms (abdominal pain, weight loss, and chronic diarrhea) also exhibited an anxiety-exacerbating effect among caregivers of CD cases. Their quality of life is known to improve once CD cases have been diagnosed and started on a gluten-free diet.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, extragastrointestinal manifestations comprise fatigue, anemia, infertility, hepatic disorders, neuropsychiatric symptoms and depression. All in all, CD negatively impacts the quality of welling for CD patients [7] and their caregivers [8].…”
Section: Introductionmentioning
confidence: 99%